Avaliação hematológica, bioquímica e hemogasométrica de sangue caprino armazenado em bolsas CPDA-1 E CPD/SAG-M - Tavares, Marcondes Dias (Universidade Federal Rural do Semi-Árido, 2013)
The present study aimed to evaluate the hematological, biochemical and hemogasometric changes in caprine blood stored in CPDA-1 and CPD/SAG-M bags. Seven male, adult, neutered, mixed breed goats weighing an average of 45kg were used. From each animal, 25% of the estimated total blood volume was collected into two plastic bags, one containing CPDA-1 and another with CPD/SAG-M; next they were stored for 42 days. Hematological (number of erythrocytes, packed cell volume, total and plasmatic hemoglobin, degree of hemolysis, mean cell volume, leukocytes), biochemical (glucose, lactate, sodium, potassium, total plasma protein), hemogasometric (pH, bicarbonate, partial pressure of oxygen, partial pressure of carbon dioxide, oxygen saturation, base deficit, total carbon dioxide) and microbiological evaluations were performed in seven moments (T), T0 (immediately after sampling), T7 (seven days), T14 (fourteen days), T21 (twenty-one days) , T28 (twenty-eight days), T35 (thirty-five days) and T42 (forty-two days after sampling). In the two bags there was an increase of plasmatic hemoglobin, degree of hemolysis, lactate, pO2 and a decrease of total hemoglobin and pH. In the bags there was no alteration in the erythrocyte count, glucose, sodium, potassium or partial pressure of carbon dioxide. In the comparison with the CPDA-1, the CPD/SAG-M bag had lower erythrocytes, packed cell volume, total hemoglobin and sodium, as well as higher levels of hemolysis and plasmatic hemoglobin. The changes observed in the caprine blood stored for 42 days in CPDA-1 and CPD/SAG-M bags were not sufficient to invalidate their use as a therapeutic resource, however, it has been found that it is preferable to use CPDA-1 bags for the conservation of caprine blood
Hematologic, biochemical and hemogasometric evaluation of caprine blood stored in CPDA-1 and CPD/SAG M bags
Keywords: Caprino- blood; Erythrocytes; Hematology; Caprino- Sangue; Eritrócitos; Hemoterapia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA